The Correlation Between Gender and Narrative Story In Student Listening Skill - Suci Alawiyah; Lidyatul Izzah (Universitas Cokroaminoto Palopo, 2023)
The purpose of this study was to determine the correlation between gender and narrative stories with students' listening skills. The research will be held in the second semester of grade eight students of SMPN 3 TANGSEL. The method of this study is a quantitative method. The results are there are 68% of female students who have an interest and ability in narrative stories through listening skills while only 32% of boys. There is a significant positive and significant relationship between genre and narrative story on the listening skills of 9th graders (1) SMPN 3 Tangerang Selatan City with r count greater than r table (0.773 > 0.148) and a significance value of 0.000 which means less than 0.05 (0.000 < 0.05). Thus, the genre and narrative story variables together have an important role in improving students' ability to write suggestive narratives. So based on the results of the research, gender has a significant correlation with students' listening skills in narrative stories.